Interpersonal Communication Goals BPJS Kesehatan dalam Penanganan Pengaduan Peserta - Mufid Salim; Nadila Wahyuni; Rustono Farady Marta; Nunik Hariyanti; Fitrinanda An Nur (Institut Pertanian Bogor, 2023)
One of the Social Security Administering Agency of Health Insurance (BPJS Kesehatan) duties is to handle complaints submitted by its participants. This study aims to analyze how the complaints by the BPJS Kesehatan of the Solok branch office to its participants through interpersonal communication are based on emphasizing interpersonal communication. This study uses data collection methods with structured interviews with the BPJS Kesehatan and with the three participants who submitted complaints according to the researcher's needs, then the method of observation and documentation. Researchers use data reduction, data presentation, and verification techniques for data analysis, while data validation techniques use triangulation, which checks data from various sources. This study indicates that the purpose of interpersonal communication can be achieved through several aspects of communication, namely emphasis on interpersonal needs, emphasis on communication channels, emphasis on messages, emphasis on listening skills, and emphasis on feedback. From the five aspects of interpersonal communication emphasized, it was found that the purpose of the BPJS Kesehatan interpersonal communication on its participants is to understand the information or messages conveyed and change attitudes.